Odpowiedź:
a)
x + y = 7
x = 2
2 + y = 7
y = 7 - 2 = 5
odp: x = 2 , y = 5
b)
2a - 3b = - 14
a = - 2b
2(- 2b) - 3b = - 14
- 4b - 3b = - 14
- 7b = - 14
7b = 14
b = 14/7 = 2
a = - 2b = - 2 * 2 = - 4
odp: a = - 4 , b = 2
c)
l = k + 4
2k + l = 13
2k + k + 4 = 13
3k = 13 - 4 = 9
k = 9/3 = 3
l = k + 4 = 3 + 4 = 7
odp: k = 3 , l = 7\
d)
y - 2x = 5
2y + x = 10 | * 2
y - 2x = 5
4y + 2x = 20
dodajemy równania
y + 4y - 2x + 2x = 5 + 20
5y = 25
y = 25/5 = 5
y - 2x = 5
5 - 2x = 5
- 2x = 5 - 5 = 0
x = 0
odp: x = 0 , y = 5